Respuesta :
60 + 90
GCF = 30
(30 * 2) + (30 * 3) = 30(2 + 3) <== the correct way
The mistake Axial made was he did not pick the greatest common factor...he picked 3 instead of 30.
GCF = 30
(30 * 2) + (30 * 3) = 30(2 + 3) <== the correct way
The mistake Axial made was he did not pick the greatest common factor...he picked 3 instead of 30.
Answer:
Given expression,
60 + 90,
∵ 60 = 2 × 2 × 3 × 5,
90 = 2 × 3 × 3 × 5,
Thus, GCF( 60, 90) = 2 × 3 × 5 = 30,
So, we can write,
60 = 30 × 2 and 90 = 30 × 3,
∴ 60 + 90 = 30 × 2 + 30 × 3 = 30( 2 + 3 )
Hence, he had the mistake in finding the GCF of 60 and 90 i.e. he should write 30( 2 + 3 ) instead of 3(20+30)